FEMINISME DALAM KEHIDUPAN MASYARAKAT - Bambang Purwanto (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
Feminist is a method that is used in this writing. The application of this method is to express that man and woman have right to make their own decisions. Both of them will respect and understand. They will have responsibility for everything they have done. This method is also expressing that human have freedom in their life. Sometimes, some persons never understanding this method, they will always push women to do something they do not like. This think happen in a few years ago and at present, women will do many things to get the same position with men. Feminist approach shows that women wanted to destroy the patriarchy of man. They insist that man can respect woman’s opinion. They also want to stress that every opinion is not childish. Some men also think that women will go under men but they cannot see the respect of women. Respect and Friendship are the most important think and all women want to get that from men. At present, some women would like to show that feminist method can work and they insist men to respect it. Although they do it but they never forget friendship as one way to destroy conflict when it happen.